Paleomagnetic study on mid-Paleoproterozoic rocks from the Rio de la Plata craton: Implications for Atlantica - Rapalini, Augusto Ernesto; Bettucci Sanchez, Leda; Badgen, Ezequiel; Vasquez, Carlos Alberto (Gondwana Research)
The first successful paleomagnetic study on middle Paleoproterozoic rocks from the Rio de la Plata craton is reported. Samples collected from the Soca and Isla Mala granitic bodies, located in southern Uruguay, provided characteristic remanences that were used to compute the first paleomagnetic poles for the craton for ca. 2.05-2.02. Ga. The poles were complemented by a virtual geomagnetic pole from the slightly older Marincho and Mahoma complexes. The paleomagnetic results suggest fast apparent polar wander at high paleolatitudes for the Rio de la Plata craton. Comparison with coeval poles from the Guiana, Congo-São Francisco and West African cratons indicates that a configuration of Atlantica that resembles their Western Gondwana fit is not supported by paleomagnetic data. The geologic similarities in these four cratons are supportive of a major crustal forming event between 2.2-2.0. Ga. A modified configuration for Atlantica is proposed that is consistent with our new (and older) paleomagnetic data. Atlantica was assembled at 2.1-2.05. Ga at polar latitudes and drifted towards the equator soon afterwards. Fil: Rapalini, Augusto Ernesto. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Geociencias Básicas, Aplicadas y Ambientales de Buenos Aires. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Geociencias Básicas, Aplicadas y Ambientales de Buenos Aires; Argentina Fil: Bettucci Sanchez, Leda. Universidad de la República; Uruguay Fil: Badgen, Ezequiel. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Geociencias Básicas, Aplicadas y Ambientales de Buenos Aires. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Geociencias Básicas, Aplicadas y Ambientales de Buenos Aires; Argentina Fil: Vasquez, Carlos Alberto. Consejo Nacional de Investigaciones Científicas y ...